THE CORRELATION BETWEEN UNDERGRADUATE EFL STUDENTS’ READING HABIT AND LINGUISTIC INTELLIGENCES - Susanta, Mulyana; Tridinanti, Gaya; Sari, Farnia; Dianti, Rahma (English Community Journal, 2021)
The aim of this study was to find out whether there was significantly correlation and contribution or not between reading habit and linguistic intelligence.Seventy two students as sample by using intact sampling technique. The  method of this study was correlational research. In analyzing the data, correlation analysis and regression analysis were used.It was found that the correlation coefficient or the r-value (0.361) was higher than r-table (0.228). Then, the level of probability (p) significance (sig.2-tailed) was 0.000. It means that p-value (0.002) was lower than 0.05.Inanalyzing the data of regression analysis, it was found that the students’ reading habit contributed students’ linguistic intelligence significantly with tvalue (3.234) was higher than ttable (1.667) with sig.value (0.002) was lower than probability (0.05). It means that students’ reading habit support significant effect in the level of 13% toward linguistic intelligence.Itcanconcluded that there was a significant correlation and contribution between reading habit and linguistic intelligences.